Atomically dispersed Co-Cu dual active sites in carbon networks as an efficient oxygen electrocatalyst - Sinha, Nibedita; Das, Chandni; Pal, Santanu; Urkude, Rajashri R.; Ahmed, Tanbir; Ghosh, Biplab; Roy, Poulomi (Dalton Transactions, 2025)
Single-atom metal-based electrocatalysts offer extended advantages by maximizing the utilization of active sites but often suffer from complex synthesis processes and low-density metal loading. The present work showcases a strategic design for integrating highly dense cobalt-copper dual atoms dispersed on a nitrogen-rich porous carbon network (CoCu-NGC). The atomically dispersed CoCu-NGC outperforms the ORR and OER activities of their single metallic counterparts (Co-NGC or Cu-NGC) and conventional noble-metal based electrocatalysts (Pt/C and RuO2). Benefitting from the electronic modulation in the dual SAC system, the CoCu-NGC displayed outstanding bifunctional performance with low Delta E values of 0.69 V in freshwater and 0.78 V in seawater, highlighting it as a potential alternative to the costly state-of-art electrocatalysts.

Amorphous vanadium-doped iron borate/tetraboride hybrid as an efficient electrocatalyst for the oxygen evolution reaction - Ahmed, Tanbir; Pal, Santanu; Sinha, Nibedita; Das, Chandni; Roy, Poulomi (Dalton Transactions, 2026)
The design of an effective electrocatalyst as a replacement for a conventional expensive electrocatalyst for facilitating the sluggish oxygen evolution reaction (OER) at the anode has been identified as an effective way to make hydrogen production economical. Herein, we have developed a unique combination of iron borate and iron tetraboride (Fe-BO/FeB) by a facile chemical reduction process. The optimum vanadium doping further led to the transformation of Fe-BO/FeB into an amorphous form, which is believed to be very beneficial for the OER mechanism. The developed electrocatalyst needs overpotentials of 215 mV and 256 mV in alkaline 1 M KOH electrolyte to achieve current densities of 10 and 100 mA cm-2, respectively, and it also shows stability over 48 h, maintaining a high current density of 200 mA cm-2. Enhanced performances were also confirmed by smaller activation energies for the optimized sample compared with a pristine electrocatalyst.